Do Customer Satisfaction and Trust Mediate the Relationship of Ethical Behavior to Customer Loyalty? Empirical Study of Indonesian Textile B2B Customer - Ikramina Larasati Hazrati Havidz; Laila Fazrin; Tantri Yanuar Rahmat Syah; Rojuaniah; Mufridah Nur (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
It is very important to retain loyal customers rather than looking for new ones. Customer loyalty is influenced by the seller's ethical behavior and customer satisfaction with the seller. Meeting and exceeding customer expectations is a challenge in a competitive industry. Including the business to business (B2B) sector which works under industrial pressure. This research aims to explore the relationship between ethical behavior and satisfaction. Trust, and loyalty. This research was conducted on 111 business to business (B2B) textile customers in Indonesia. The structural equation modeling (SEM) method was used to analyze the collected data. This research shows that compliance with sales ethical standards has a significant impact on customer loyalty, satisfaction and competitive advantage if the service provided meets customer expectations and the information provided matches product availability. Additionally, ethical sales behavior shapes customer loyalty by building trust and long-term relationships.